Interhemispheric and longitudinal differences in the ionosphere–thermosphere coupling process during the May 2024 superstorm - WenBo Li; LiBo Liu; YuYan Yang; TingWei Han; RongJin Du; RuiLong Zhang; HuiJun Le; YiDing Chen (Earth and Planetary Physics)
Geomagnetic storm events have a strong influence on the ionosphere–thermosphere (I-T) coupling system. Analyzing the regional response process of the I-T system and its differences across the northern and southern hemispheres is an important but challenging task. In this study, we used a combination of multiple observations and a model simulation to examine the north–south hemispheric difference in the I-T coupling system in the American and Asian sectors during the geomagnetic superstorm that occurred in May 2024. Observations of the total electron content (TEC) showed that the Asian sector had negative storms in the northern hemisphere and positive storms in the southern hemisphere, a process that exacerbated the hemispheric differences in the TEC. However, both hemispheres of the American sector showed negative storms. The thermospheric composition changes also differed between the two sectors, and their variation could partially explain the hemispheric differences caused by positive and negative storms. Moreover, the influence of the thermospheric density change was less than that of the thermospheric composition. Finally, the dynamic effect of the thermospheric wind and the plasma transport processes strongly modulated the north–south differences in the TEC at nighttime in the American and Asian sectors, respectively, during this superstorm.